Occupational and Educational Expectations of Rural youth in Croatia - Buzov, Ivanka; Batarelo Kokić, Ivana; L. Kurz, Terri (Revija za elementarno izobraževanje, 2021)
The present study is as an attempt to understand how socio-demographic characteristics (i.e., gender, family socioeconomic status) and school level supports (i.e., school climate, professional guidance at school) influence occupational and educational expectations among rural youth (i.e., aspirations for a meaningful career, future family values, and future employment goals). The findings showed a relationship among the demographic characteristics, school level supports, career aspirations and future family and employment expectations of rural youth. The results of regression analysis indicate that school climate does influence aspirations towards a meaningful career, future family orientation and future employment goals. In addition, aspirations towards a meaningful career are also influenced by gender and professional guidance at school.
Keywords: educational expectations; family values; professional expectations; rural youth; school climate